3D animation as an alternative mean of da'wah for children - Draman, Mohd Zharif; Zeki, Akram M. (IEEE, 2014)
3D animation cartoons has prodigious influence on children's mind, because children love watching cartoon. It is proved to influences family functioning in varied ways and has shaped our culture and social system. It affects the new generation with more aggressive personality and negative minds in sociality. Hence, it obstructed their learning of right behaviors. Concerned that this problem might become more severe, we tried relieve these problems by using a more proper 3D animation cartoon for children's entertainment as it is the closest media to the children. We have been motivated to propose a proselytizing or preaching of Islam (Da'wah) to prevent negative influences towards the children by proposing a suitable guideline for 3D animator in producing da'wah animation media more effectively.